SOCIAL IMPACT ANALYSIS OF AGRICULTURAL PROGRAMS IN WEST ACEH USING A SOCIAL RETURN ON INVESTMENT APPROACH - Dedy Darmansyah; Rusdi Faizin; Andriyono Kilat Adhi; Burhanudin; Ina Yuyun; Cut Salsabila (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2026)
West Aceh Regency has significant potential in the agricultural sector, which has been the focus of various government development programs. However, evaluation of the impact of these programs has been predominantly based on quantitative indicators and has not fully captured the resulting social value. The Social Return on Investment (SROI) approach presents a method capable of comprehensively measuring the social, economic, and environmental value of an intervention. Therefore, this study aims to analyze the social impact of agricultural programs implemented in West Aceh, calculate the program's Social Return on Investment (SROI) ratio, and formulate data-based recommendations for future program improvements. This research method consists of four main stages. The first stage is Program Identification and Data Collection. The second stage is Program Impact Identification. The third stage includes Social Return on Investment (SROI) Analysis, namely the calculation of the Social Return on Investment (SROI) ratio. Finally, the fourth stage is validation of the analysis results. The results of this study conclude that the agricultural programs implemented in West Aceh Regency have had positive and sustainable social and economic impacts on the beneficiary communities. The calculation results show a Social Return on Investment (SROI) of 1.09:1, meaning that every Rp 1 of government investment generates Rp 1.09 worth of social benefits. This value indicates that the program has been socially effective and has made a significant contribution to improving farmer welfare.